โครงสร้างความสัมพันธ์ปัจจัยเชิงสาเหตุและผลของความเป็นอันหนึ่งอันเดียวกับองค์การของครูในสังกัดสถาบันการอาชีวศึกษาในเขตกรุงเทพมหานครและปริมณฑล: Structural Relationships of the Antecedents and Effects of Organizational Identification of Teachers in Institute of Vocational Education in Bangkok and Perimeter - Wisut Srinual วิสุทธิ์ สีนวล (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2020)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาโครงสร้างความสัมพันธ์ปัจจัยเชิงสาเหตุและผลของความเป็นอันหนึ่งอันเดียวกับองค์การของครูในสังกัดสถาบันการอาชีวศึกษาในเขตกรุงเทพมหานครและปริมณฑล ตัวอย่างในการวิจัยเป็นครูในสังกัดสถาบันการอาชีวศึกษาในเขตกรุงเทพมหานครและปริมณฑล จำนวน 544 คน ที่ได้จากการสุ่มตัวอย่างแบบหลายขั้นตอน เก็บข้อมูลโดยใช้แบบวัด 7 ฉบับ มีค่าความเชื่อมั่นแบบสอดคล้องภายในอยู่ตั้งแต่ 0.845-0.953 ในการวิเคราะห์ข้อมูลใช้สถิติเชิงบรรยาย การวิเคราะห์ความเที่ยงตรงเชิงโครงสร้างโดยการวิเคราะห์องค์ประกอบเชิงยืนยัน และการวิเคราะห์โครงสร้างความสัมพันธ์ปัจจัยเชิงสาเหตุ ผลการวิจัยสรุปได้ว่า โครงสร้างความสัมพันธ์ปัจจัยเชิงสาเหตุและผลของความเป็นอันหนึ่งอันเดียวกับองค์การของครูในสังกัดสถาบันการอาชีวศึกษาในเขตกรุงเทพมหานครและปริมณฑลมีความกลมกลืนกับข้อมูลเชิงประจักษ์หลังจากการปรับโมเดลในระดับที่ยอมรับได้ (X2= 599.74, df= 152; p-value< 0.01, SRMR= 0.042, RMSEA= 0.070, GFI= 0.91, NFI= 0.97, CFI= 0.98, NNFI= 0.97, PNFI= 0.78) ผลการทดสอบเส้นอิทธิพลพบว่า ความเป็นอันหนึ่งอันเดียวกับองค์การได้รับอิทธิพลทางบวกโดยตรงจากภาวะผู้นำเชิงจริยธรรม และการรับรู้ชื่อเสียงจากภายนอก ซึ่งตัวแปรเหล่านี้ร่วมกันอธิบายความเป็นอันหนึ่งอันเดียวกับองค์การได้ร้อยละ 43 ตัวแปรพฤติกรรมการทำงานอย่างมีจริยธรรมได้รับอิทธิพลทางบวกโดยตรงจากความเป็นอันหนึ่งอันเดียวกับองค์การและภาวะผู้นำเชิงจริยธรรม รวมทั้งได้รับอิทธิพลทางบวกโดยอ้อมจากภาวะผู้นำเชิงจริยธรรม และการรับรู้ชื่อเสียงจากภายนอก ซึ่งตัวแปรเหล่านี้ร่วมกันอธิบายความยึดมั่นผูกพันในการทำงานได้ร้อยละ 42 ตัวแปรพฤติกรรมการเป็นสมาชิกที่ดีขององค์การได้รับอิทธิพลทางบวกโดยตรงจากความเป็นอันหนึ่งอันเดียวกับองค์การและการรับรู้ชื่อเสียงจากภายนอก รวมทั้งได้รับอิทธิพลทางบวกโดยอ้อมจากจากภาวะผู้นำเชิงจริยธรรม และการรับรู้ชื่อเสียงจากภายนอก ซึ่งตัวแปรเหล่านี้ร่วมกันอธิบายพฤติกรรมการเป็นสมาชิกที่ดีขององค์การได้ร้อยละ 52 ส่วนตัวแปรความตั้งใจออกจากวิชาชีพได้รับอิทธิพลทางลบโดยตรงจากความเป็นอันหนึ่งอันเดียวกับองค์การ รวมทั้งได้รับอิทธิพลทางลบโดยอ้อมจากจากภาวะผู้นำเชิงจริยธรรม และการรับรู้ชื่อเสียงจากภายนอก ซึ่งตัวแปรเหล่านี้ร่วมกันอธิบายความตั้งใจออกจากวิชาชีพได้ร้อยละ 6 The purpose of this study was to examine the structural relationships of the antecedents and effects of organizational identification of teachers in institute of vocational education in bangkok and perimeter. The samples were selected by multi-stage sampling. The population consisted of teachers in institute of vocational education in bangkok and perimeter. The total sample in this study was consisted of five hundred and forty four individuals. There were seven tests the questionnaire with an internal consistency reliability of 0.845-0.953. The descriptive statistics were analyzed by SPSS for Windows while confirmatory factor analysis and structural relationship were analyzed by LISREL. The research findings were as follows: The hypothesized structural relationships of the antecedents and effects of organizational identification of teachers in institute of vocational education in bangkok and perimeter was adjusted in harmony with the fitted empirical data (X2 = 599.74, df= 152; p-value< 0.01, SRMR= 0.042, RMSEA= 0.070, GFI= 0.91, NFI= 0.97, CFI= 0.98, NNFI= 0.97, PNFI= 0.78). In terms of organizational identification, the variables that had direct positive effects: ethical leadership and perceived external prestige. These variables accounted for forty three percent of the variance of the aspect of organizational identification. For the factor of ethical work behavior, the variables which had direct positive effects was organizational identification and ethical leadership. In addition, the variables which had indirect positive effects were: ethical leadership and perceived external prestige. These variables accounted for forty two percent of the variance in terms of ethical work behavior. For the factor of organizational citizenship behavior, the variables which had direct positive effects were: organizational identification and perceived external prestige. In addition, the variables which had indirect positive effects were: ethical leadership and perceived external prestige. These variables accounted for fifty two percent of the variance of organizational citizenship behavior. With regard to intention to leave teaching profession, the variables which had direct negative effects was organizational identification. In addition, the variables which had indirect negative effects were: ethical leadership and perceived external prestige. These variables accounted for six percent of the variance of intention to leave teaching profession.